Data-driven process to improve VA surgical flow. Issue 4 (14th May 2018) - Bidassie, Balmatee; Gunnar, William; Starr, Leigh; Van Buskirk, George; Warner, Lisa; Anckaitis, Clifford; Howard, Angela
Abstract : Purpose: During years 2014-2016, Veterans Health Administration National Surgery Office conducted a surgical flow improvement initiative (SFII) to assist low-performing surgery programs to improve their operating room efficiency (ORE). The initiative was co-sponsored by VHA National Surgery Office and VHA Office of Systems Redesign and Improvement. The paper aims to discuss this issue. Design/methodology/approach: An SFII algorithm, based on first-time-start (FTS), cancellation rate (CR), lag time (LT) and OR utilization, assigned an ORE performance Level (1-low to 4-high) to each VA Medical Center (VAMC). In total, 15 VAMCs with low-performance surgery programs participated in SFII to assess the current state of their surgical flow processes and used redesign methods to focus on improvement objectives. Findings: At the end of the project, 14 VSAs, 40 RPIWs, 45 "90-day projects" and 73 Just-Do-It's were completed with 65 percent (158/243) improvement actions and 86 percent sites improving/sustaining all four ORE metrics. There was a statistically significant difference in improvement across the three stages (baseline, improvement, sustain) for FTS (45.6-68.7 percent; F =44.74; p <0.000); CR (16.1-9.5 percent; F =34.46; p <0.000); LT (63.1-36.3 percent; F =92.00; p <0.000); OR utilization (43.4-57.7 percent; F =6.92; p <0.001) and VAMC level (1.7-3.65; F =80.11; p <0.000). The majority developed "fair to excellent" sustainment (91 percent) and spread (82 percent) plans. The projected annual estimated return-on-investment was $27, 949, 966. Originality/value: The SFII successfully leveraged a small number of faculty, coaches, and industrial engineers to produce significant improvement in ORE across a large national integrated health care network. This strategy can serve healthcare leaders in managing complex healthcare issues in their facilities.